2006
DOI: 10.1111/j.1365-3032.2006.00525.x
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐lethal responses of the large pine weevil, Hylobius abietis, to the pyrethroid insecticide lambda‐cyhalothrin

Abstract: The response of the large pine weevil (Hylobius abietis) to the pesticide lambda‐cyhalothrin, a pyrethroid, is investigated. Both behavioural (feeding preferences) and nutritional and physiological (lipid content) responses are recorded. Hylobius abietis shows both a significant avoidance of pesticide‐treated food sources and a decrease in lipid content after exposure, but a full recovery after feeding on untreated food. It is proposed that the mechanism for the pesticide avoidance and altered lipid levels is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Additionally, Simões et al (2000) showed that Galleria melonella infected with S. carpocapsae had reduced silk production. Chemical insecticides also have sub-lethal effects on insects, including on H. abietis (Rose et al, 2006). However, it has not previously been investigated whether exposure of H. abietis to sublethal concentrations of EPN has behavioral effects on the insect.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Simões et al (2000) showed that Galleria melonella infected with S. carpocapsae had reduced silk production. Chemical insecticides also have sub-lethal effects on insects, including on H. abietis (Rose et al, 2006). However, it has not previously been investigated whether exposure of H. abietis to sublethal concentrations of EPN has behavioral effects on the insect.…”
Section: Introductionmentioning
confidence: 99%
“…The antifeedant effects of sublethal λ ‐cyh were observed in other insect species as well, such as B . terrestris , Bemisia tabaci , O. excavate , and Hylobius abietis 12,14,32,33 . Meanwhile, after being transferred to non‐toxic mulberry leaves, silkworm larvae treated with λ ‐cyh LC 1 , LC 10 , and LC 20 showed varied degrees of recovery, but stunted growth persisted in the LC 50 treated group.…”
Section: Discussionmentioning
confidence: 99%
“…This may reduce residual exposure, because the insects avoid treated/exposed surfaces. However, insects may also increase activity if they encounter surfaces with adhered pyrethroids (Alzogaray et al 1997; Rose et al 2006; Prasifka et al 2008), which points to an increased residual uptake. For a specific risk assessment, including both residual and oral exposure, this may diminish the differences in vulnerability between species.…”
Section: Discussionmentioning
confidence: 99%